The Role and Content of Cultural Competence in the Formation of Pedagogical Professional Competence (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the concept and content of cultural competence. The importance of the cultural approach and its role in the formation of the professional competence of today's literature teachers have been expressed. Different and important aspects of new pedagogical technology from other pedagogical approaches will be highlighted on the basis of examples.